2018
DOI: 10.1007/s00167-018-5256-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific instrumentation improved axial alignment of the femoral component, operative time and perioperative blood loss after total knee arthroplasty

Abstract: PurposeThe purpose of the present study was to compare patient-specific instrumentation (PSI) with standard instrumentation (SI) in patients undergoing total knee arthroplasty (TKA). PSI is hypothesized to have advantages with respect to component alignment; number of outliers (defined as alignment > 3° from the target alignment); operative time; perioperative blood loss; and length of hospital stay. This new surgical technique is expected to exhibit superior performance.MethodsA total of 23 randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 62 publications
3
44
0
1
Order By: Relevance
“…Nonetheless, there are still a number of patients that suffer from postoperative pain and persistent limited range of movement [ 1 , 15 ] In order to improve the overall outcome of patients novel PSI have been developed. Gong et al have recently demonstrated that patient-specific instrumentation is associated with improved axial alignment of the femoral component, operative time and perioperative blood loss after TKA [ 16 ]. Further, Leon-Munoz et al have reported that patient-specific instrumentation might reduce operative time, could reduce perioperative blood loss and provides logistical benefits in the operation room [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, there are still a number of patients that suffer from postoperative pain and persistent limited range of movement [ 1 , 15 ] In order to improve the overall outcome of patients novel PSI have been developed. Gong et al have recently demonstrated that patient-specific instrumentation is associated with improved axial alignment of the femoral component, operative time and perioperative blood loss after TKA [ 16 ]. Further, Leon-Munoz et al have reported that patient-specific instrumentation might reduce operative time, could reduce perioperative blood loss and provides logistical benefits in the operation room [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, Leon-Munoz et al have reported that patient-specific instrumentation might reduce operative time, could reduce perioperative blood loss and provides logistical benefits in the operation room [ 17 ]. However, no significant differences were found between patient-specific instrumentation and standard instrumentation with respect to alignment of the remaining components, number of outliers or length of hospital stay [ 16 ]. Nonetheless, most of the available studies focus on patient-specific instruments rather than on instruments and the patient-specific implants.…”
Section: Discussionmentioning
confidence: 99%
“…We created a risk of bias table that included the following contents: details on methods of random sequence generation, allocation concealment, blinding, incomplete outcome data, selective outcome reporting, and other bias. The overall quality of each study was evaluated as “low risk of bias,” “high risk of bias,” or “unclear risk of bias.” A modified Jadad 7‐point scale was used to assess the quality of RCTs, and a score of <4 points was regarded as low quality 13 . If the number of included RCTs was ≥10, the publication bias was assessed by funnel plot 14 …”
Section: Methodsmentioning
confidence: 99%
“…However, there is ongoing debate on the efficacy. Some groups show advantages of patient-specific instrumentation for alignment of some but not all prosthesis components as well as for reduction of operative time and perioperative blood loss, but no difference in the length of hospital stay [17]. Contradictorily, other groups report that patient-specific instrumentation does not result in clinically meaningful improvement in alignment, fewer outliers, or better early Given the requisite industrial background and legal considerations in the production and distribution of medical products for permanent or temporary use in patients, widespread on-site manufacturing of metal implants or plastic guides is not yet implemented and radiologists need merely provide ideal 3D-source imaging, as described above.…”
Section: Exemplary Applications Of Medical Three-dimensional Printingmentioning
confidence: 99%